2022
DOI: 10.3390/ijerph192114406
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Supply in the Region of Antofagasta (Chile): A Challenge between Past, Present and Future

Abstract: Since the mid-nineteen century, when the first mining companies were established in the region of Antofagasta to extract saltpeter, mining managers and civil authorities have always had to face a number of problems to secure a water supply sufficient for the development of industrial activities and society. The unique features of the region, namely the scarcity of rainfall, the high concentration of arsenic in freshwaters and the increasing pressure of the mining sector, have made the supply of drinking water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Therefore, data standardization was used as described in Equation ( 1), which was not developed to discard data with a 0 value. This partially supports choosing RF as the algorithm to generate the predictive models, since this algorithm shows greater tolerance to input data errors, as indicated by previous studies, such as [28][29][30].…”
Section: Data Standardizationsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, data standardization was used as described in Equation ( 1), which was not developed to discard data with a 0 value. This partially supports choosing RF as the algorithm to generate the predictive models, since this algorithm shows greater tolerance to input data errors, as indicated by previous studies, such as [28][29][30].…”
Section: Data Standardizationsupporting
confidence: 68%
“…Loa River receives surface and groundwater from Salado River, located near Chiu Chiu. Salado River is a tributary of El Tatio geothermal field and is known for its high concentrations of arsenic (As), being the main source of this toxic metal in the Loa River basin [29].…”
Section: Study Areamentioning
confidence: 99%
“…From the point of view of water quality, studies from 2006 to 2016 showed that the drinking water quality in Antofagasta was acceptable based on the guidelines because there were no significant differences observed between the types of water and only a few minor breaches were observed compared with other regions in Chile. In our study, the population was derived from urban zones where the drinking water quality is similar to that of other countries [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt, Zinc, iron, Cadmium, gold [3]…The historic shortage of fresh water is currently aggravated by the effects of climate change [4]. Secondly, the region's surface watercourses are not only rare, but also of poor quality, due to their high salinity and high chemical element content [5] in view of the negative impact of the fact that the region is a significant reserve of copper, lithium, molybdenum, and natural nitrates [6]. Today, new housing developments require private water supply either by manual or industrial drilling, the depths of which vary from one region to another and whose supply network uses polyvinyl chloride (PVC) pipes, abandoning such as galvanized pipes.…”
Section: Introductionmentioning
confidence: 99%